Relationship Support Relationship, Economic Status And Mother Attitudes In Fertile Age Couples (EFA) In Iva Examination To Detect Cervical Caps In Puskesmas Pulo Brayan (JURNAL PROTEKSI KESEHATAN, 2020)
Each year more than 300,000 women die from cervical cancer more than half a million women are diagnosed. Every minute, a woman is being ionogized. Cervical cancer is one of the biggest threats to women's health. Method; analytical survey research method with cross sectional approach. The population of this study were all women of childbearing age in the work area  , totaling 117 people with a sample size of 54 respondents using proportional stratified random sampling technique. Sempel used the total population technique, namely the entire population of the chi-square statistical test. . Result; results of statistical tests, namely the Chi-square, concluded that there was a relationship between husband's support and IVA examination at PUS (p = 0.006 α 0.05), which means that economic status has no influence on the effect of IVA on EFA. and (p = 0.006